Profile of soluble cell adhesion molecules as potential biomarkers in the cardiac stages of chronic Chagas disease - Vaitkevicius-Antão, Victor; Silva, Bruno Almeida; Barros, Michelle da Silva; Costa-Oliveira, Cíntia Nascimento da; Torreão, Byannca de Carvalho; Silva, Ana Carla da; Martins, Silvia Marinho; Carrazone, Cristina; Oliveira, Wilson; Medeiros, Carolina de Araújo; Rabello, Michelle Christiane da Silva; Lorena, Virginia Maria Barros de (Frontiers in Immunology, 2025)
Chagas cardiomyopathy is the most severe chronic manifestation and leading cause of mortality in the disease. Chronic inflammation, resulting from persistent infection by T. cruzi, leads to continuous immune system activation in patients with Chagas disease. The knowledge of immunological aspects can be important for the identification of biomarkers capable of indicating parasitological cure or clinical progression provides for physician’s valuable tools for improved clinical evaluation. Soluble cell adhesion molecules (sCAMs) have been applied in other disease like potential biomarkers. Thus, the aim of this study was to evaluate the levels of soluble cell adhesion molecules in chronic patients with different stages of Chagas heart disease progression. Sera from 303 individuals, classified according to cardiac involvement and left ventricular dysfunction, were used for cell adhesion molecules quantification (sVCAM-1, sP-selectin, sE-selectin and sL-selectin) and it was measured using the Cytometric Bead Array. We found that sCAMs demonstrated good performance in differentiating patients in the indeterminate phase from negative individuals or those in the mild cardiac phase, as well as patients with mild from those with severe cardiomyopathy, and cardiac patients non-infected versus infected (severe cardiomyopathy). Therefore, sCAMs may serve as potential biomarkers for the diagnosis and prognosis of chronic cardiac patients with Chagas disease.